2023
DOI: 10.1002/psp4.13013
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a PBPK modeling strategy to support antimalarial drug development

Nada Abla,
Eleanor Howgate,
Karen Rowland‐Yeo
et al.

Abstract: As part of a collaboration between Medicines for Malaria Venture (MMV), Certara UK and Monash University, physiologically‐based pharmacokinetic (PBPK) models were developed for 20 antimalarials, using data obtained from standardized in vitro assays and clinical studies within the literature. The models have been applied within antimalarial drug development at MMV for more than 5 years. During this time, a strategy for their impactful use has evolved. All models are described in the supplementary material and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A full PBPK model including a permeability‐limited lung compartment was used to provide a prospective prediction of pyronaridine and amodiaquine total and unbound concentrations in the lung. 29 , 30 A perfusion‐limited model was similarly used for the metabolite DEAQ. 31 Artesunate concentrations were not evaluated as this drug does not show in vitro antiviral activity against SARS‐CoV‐2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A full PBPK model including a permeability‐limited lung compartment was used to provide a prospective prediction of pyronaridine and amodiaquine total and unbound concentrations in the lung. 29 , 30 A perfusion‐limited model was similarly used for the metabolite DEAQ. 31 Artesunate concentrations were not evaluated as this drug does not show in vitro antiviral activity against SARS‐CoV‐2.…”
Section: Resultsmentioning
confidence: 99%
“…Compound files and validation data have been previously published in full. 29 Briefly, model input values for pyronaridine, amodiaquine, and DEAQ drug‐specific characteristics and PK parameters were obtained from the published literature, from in‐house data, or were predicted. All simulations were run using version 21 of the Simcyp Simulator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBPK simulations were conducted using models developed and validated for PYR and PQP with Simcyp (version 19; Certara). 32 These predicted no clinically relevant change in PYR exposure when administered with PQP (i.e., <1.25‐fold increase in PYR exposure). Moreover, a clinical DDI study showed no significant increase in PYR exposure when PYR (associated with artesunate) was administered for 3 days together with the CYP3A4 inhibitor ritonavir over 17 days in healthy volunteers.…”
Section: Discussionmentioning
confidence: 96%
“…17 , 18 Furthermore, physiologically‐based pharmacokinetic (PBPK) modeling of potential PK drug–drug interactions (DDIs) using the known properties of the two compounds predicted no significant interaction at therapeutic drug exposures (N. Abla, personal communication). 32 This phase I study in healthy adults investigated the safety, tolerability, and PKs of PYR and PQP following co‐administration and when administered alone in comparison to placebo.…”
Section: Introductionmentioning
confidence: 99%